Lessons Learned and Software Process Improvement - Bayona Oré, Sussy (2017)
Current methods focus on the aspects related to the lessons learned, feedback and information sharing, however many organizations do not establish feedback mechanisms for organizational learning with the lessons learned as a result of process deployment initiatives participation. This paper describes the steps in order to identify the lessons learned as a result to put in practice the processes. It also provides a practical analysis of lessons learned identified in software process deployment initiatives in order to improve the knowledge in the organizations.